Frecuency of use and values of em plan in spontaneous and semi-structured conversations: Bilingual Spanish-Catalan speakers in Catalonia - Valero Fernández, Pilar; Kim, HeeSoo (Círculo de Lingüística Aplicada a la Comunicación, 2026)
The focus of our research is on the various communicative functions performed by the discourse marker en plan. To achieve this, we analyse the six functions of this marker as identified in this research corpus consisting of five conversations. Each conversation lasted approximately 20 minutes, with three being spontaneous and two being semi-directed. The participants in these conversations included four women and two men of Catalan and Spanish-Catalan bilingual origin. In the corpus, en plan acts as an intensifier, exemplifier, reformulator, introducer, approximator, and filler formula. Its frequent presence in colloquial discourse in the communication channel, mainly for young people, of the current peninsular Spanish used in this Autonomous Community is verified by means of 77 registers found in this corpus.